Central nervous system malformations in Mohr's syndrome. Issue 10 (October 1989) - Reardon, W; Harbord, M G; Hall-Craggs, M A; Kendall, B; Brett, E M; Baraitser, M
Abstract : A boy with severe developmental delay, bilateral, symmetrical hallucal duplication, and accessory alveolar frenula was found to have radiological evidence of a large arachnoid cyst compressing the cerebellum and brain stem. We review neurological abnormalities in Mohr's syndrome.